1994
DOI: 10.1104/pp.106.3.1007
|View full text |Cite
|
Sign up to set email alerts
|

Ozone, Sulfur Dioxide, and Ultraviolet B Have Similar Effects on mRNA Accumulation of Antioxidant Genes in Nicotiana plumbaginifolia L

Abstract: As a result of anthropogenic activities, concentrations of O3 and SO, in the lower atmosphere have increased considerably in industrialized parts of the world. Upward trends of surface UV-B radiation have been recognized and attributed to a depletion in stratospheric ozone (Lefohn, 1992). During peak episodes, atmospheric concentrations of these factors may reach levels that are toxic to plants and to which plants respond by triggering various defense mechanisms. One such response that has been invoked in seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
137
1
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(155 citation statements)
references
References 36 publications
12
137
1
1
Order By: Relevance
“…The relatively strong UV-B radiation used in the present study caused considerable cell/tissue damage on prolonged exposure, which could promote PADPRP-mediated NIC release from NAD. This is in line with the suggestion by Willekens et al [19] that certain parts of defensive metabolism occur in association with visible tissue damage. In line with the results by Green and Fluhr [32] we suggest that UV-B exposure in plants may cause increased levels of reactive oxygen species.…”
Section: Nic and Trig Levelssupporting
confidence: 93%
See 2 more Smart Citations
“…The relatively strong UV-B radiation used in the present study caused considerable cell/tissue damage on prolonged exposure, which could promote PADPRP-mediated NIC release from NAD. This is in line with the suggestion by Willekens et al [19] that certain parts of defensive metabolism occur in association with visible tissue damage. In line with the results by Green and Fluhr [32] we suggest that UV-B exposure in plants may cause increased levels of reactive oxygen species.…”
Section: Nic and Trig Levelssupporting
confidence: 93%
“…This is in line with a rapid increase in the levels of NIC and TRIG in plant tissue culture observed in the present study. Although transcription of defensive genes is rapidly induced in response to UV-B exposure [18,19], it may take some time before damage occurs, especially oxidative damage and excessive levels of thymine dimers, which may result in necrotic/apoptotic cell death. The exposure of plant tissue culture to water-soluble oxidative stressors in the growth medium is probably very efficient.…”
Section: Nic and Trig Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such photooxidative damage was greatly decreased in transgenic tobacco plants that were capable of overexpressing genes encoding the chloroplastic CuZn-SOD enzymes (Sen Gupta et al, 1993a,b). Overexpression of CuZn-SOD genes was also demonstrated in plants exposed to herbicide treatment (Perl et al, 1993), sulphur dioxide (Madamanchi et al, 1994), UV-B radiation (Willekens et al, 1994 ;Rao et al, 1996) and pathogenic infection (Mittler et al, 1996 ;Fodor et al, 1997). As shown under field conditions, chilling stress in citrus and drought stress in wheat became more pronounced in plants suffering from Zn deficiency (Cakmak et al, 1995 ;Ekiz et al, 1998).…”
Section:       mentioning
confidence: 99%
“…Both enzymatic and nonenzymatic mechanisms have evolved to protect this cell compartment from oxygen toxicity. These include antioxidants such as ascorbate, glutathione, as well as ROS-scavenging enzymes such as superoxide dismutase (SOD; EC 1.15.1.1), ascorbate peroxidase (APx; EC 1.11.1.1) and glutathione peroxidase (GSH-Px; EC 1.11.1.9) (Willekens et al 1994;Miszalski et al 2001;Mittler 2002). It is suggested that the true source of oxidative stress is not the ROS generation per se but spatiotemporal imbalance of ROS production and detoxification (Andreyev et al 2005).…”
Section: Introductionmentioning
confidence: 99%